Mother of mine [videorecording (DVD)] - Härö, Klaus; Lundqvist, Maria, 1963-; Nyqvist, Michael, 1960-2017; Majaniemi, Topi; Elliot, Adam, 1972- (Film movement series., 2007)
When nine-year-old Eero's father is killed at the beginning of World War II his mother, broken by grief, is unable to care for him. She sends Eero out of Finland to live with a family in Sweden, away from the conflict. Feeling abandoned by his biological Finnish mother, he cannot quite attach to his Swedish surrogate mother. When the war ends, and he returns to his mother in Finland, his confusion intensifies.